Research Progress in Encapsulation of Bioactive Compounds in Protein-Polysaccharide Non-covalent and Covalent Complexes - LIANG Luodan, CAO Weiwei, LI Linlin, REN Guangyue, CHEN Junliang, XU Hanshan, DUAN Xu (Shipin Kexue, 2023)
Bioactive ingredients such as polyphenols and carotenoids have various health benefits such as anti-cancer and antioxidant activities. However, bioactive components are unstable and easily damaged in the gastrointestinal environment, making them unable to fully exert their functional effects. Proteins and polysaccharides can form complexes via non-covalent or covalent interactions, which have been widely used as encapsulation materials to enhance the stability and activity of bioactive compounds. This review summarizes the types of protein-polysaccharide complexes, and describes the application of the anti-solvent, pH-driven, thermal gelation and emulsification methods for the delivery of bioactive ingredients by protein-polysaccharide complexes. It is anticipated that this review will provide a reference for the research and application of bioactive compounds encapsulated in protein-polysaccharide complexes.